2017
DOI: 10.15406/mojamt.2017.03.00037
|View full text |Cite
|
Sign up to set email alerts
|

The Progression of Neurofeedback: An Evolving Paradigm in Addiction Treatment and Relapse Prevention

Abstract: Abbreviations: TOVA, test of variables of attention; MMPI, minnesota multiphasic personality inventory; cAMP, cyclic adenosine monophosphate; CREB, camp response element binding protein; MCI, mild cognitive impairment Introduction Recognizing addiction as a public health crisisA recent report published by the Center for Behavioral Health Statistics and Quality found that approximately one in seven Americans is expected to develop a substance use disorder at some point in their lives.1 In 2015, 20.8 million peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Thus, the identification of core processes and their interactions in nonsubstance addictive behaviors is necessary not only for understanding their addictive potential but also for potentially using them as targets for clinical interventions (e.g., Dong & Potenza, 2014). Promising evidence for the usefulness of mindfulness and neurofeedback techniques in tackling the neurocognitive mechanisms of behavioral addictions stems from research in the context of SUDs (for reviews, see Garland & Howard, 2018; Martz et al, 2020; Sunder & Bohnen, 2017) where both techniques are considered successful in treating addictions.…”
mentioning
confidence: 99%
“…Thus, the identification of core processes and their interactions in nonsubstance addictive behaviors is necessary not only for understanding their addictive potential but also for potentially using them as targets for clinical interventions (e.g., Dong & Potenza, 2014). Promising evidence for the usefulness of mindfulness and neurofeedback techniques in tackling the neurocognitive mechanisms of behavioral addictions stems from research in the context of SUDs (for reviews, see Garland & Howard, 2018; Martz et al, 2020; Sunder & Bohnen, 2017) where both techniques are considered successful in treating addictions.…”
mentioning
confidence: 99%
“…This contradicted early optimistic findings related to neurofeedback in the field of substance use disorder treatment. Neurofeedback has been generally accepted for its clinical utility as an adjunct treatment to other interventions for substance use disorders, [4][5][6]8 but comparing studies and drawing conclusions about its effectiveness is difficult because of its diverse applications in terms of equipment used, populations trained, treatment protocols used and outcome measures employed.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] However, reports have been somewhat mixed. Although previous work has demonstrated that neurofeedback can prolong treatment retention, 2 improve clinical outcomes by inducing long-lasting changes in neurophysiological brain activity and improve regulatory capabilities and executive function, 7,8 other studies have shown no significant effect of neurofeedback on addictive behaviours. 2,9 In recent years, neurofeedback has been applied successfully in diverse populations of patients with substance use disorders, such as those with disorders related to various substance classes, [10][11][12] common comorbidities (including craving, abstinence rates and attention deficits) and psychopathologies (such as trauma and depression).…”
Section: Introductionmentioning
confidence: 96%